221 Camelina Meal as an Alternative Ingredient in Growing-finishing Pig Diets. (8th October 2021) - Hilbrands, Adrienne; Li, Yuzhi; Johnston, Lee; Cox, Ryan; Lazarus, William; Martin, Wayne; Forcella, Franklin; Gesch, Russ
Abstract: The objective of this experiment was to determine the most effective inclusion rate of camelina meal (CM) in growing-finishing pig diets. Pigs (n = 192; 11 wk old), balanced for sex and initial weight, were assigned to 4 dietary treatments (6 pens/treatment; 8 pig/pen). Treatments consisted of a non-GMO corn-soybean meal-based control diet (CON), and CON containing 5% CM (5%CM), 10% (10%CM), or 15% (15%CM) camelina meal. Feed deliveries and pigs were weighed every other week to calculate ADG, ADFI, and Gain:Feed on a pen basis. Focal pigs (5/treatment) were harvested at 23 wk of age at the University of Minnesota abattoir for meat quality analysis (drip loss, pH, fat depth, belly firmness, loin marbling score, shelf life) and the remaining pigs were harvested at a commercial abattoir. Before harvest, real-time ultrasonic measurements of back fat depth and loin eye area were collected on all pigs. Data were analyzed using Proc Glimmix with dietary treatment as a fixed effect and pen as the experimental unit with data collected over time considered as repeated measures. Pigs fed CON diet consumed more feed than pigs fed CM diets (P = 0.002; Table 1). Pigs fed CON diet exhibited higher (P = 0.002) ADG than pigs consuming 10%CM and 15%CM diets. These differences resulted in heavier (P = 0.003) CON-fed pigs at marketing than 10%CM or 15%CM-fed pigs. There were no significant differences in Gain:Feed, any carcass or meat quality traits analyzed (data not shown). These results suggest that supplementing 5% CM in corn-soybean meal-based diets will not negatively influence growth performance, carcass traits, or meat quality of growing-finishing pigs.